COMUNICAÇÃO INTEGRADA DE MARKETING NO SETOR ORIZÍCOLA EM SÃO BORJA - XARÃO, ARIANE D. S.; FAVA, DIOGO; MEDEIROS, FRANCIELE; CAMARGO, JANIÉLLI; GONÇALVES, MARGARIDA (Salão do Conhecimento, 2013)
Resumo